Respuestas

2012-10-24T02:51:54+02:00
2012-10-24T02:52:58+02:00

Ejercicio 1         
x-15   =   -27
x   =   -27+15   
x   =   -12
       
       
 Comprobación    
-12-15   =   -27
       
-27   =   -27
        
 
Ejercicio 2         
-11x+12   =   144
-11x   =   144-12      
-11x   =   132
x   =   132/-11
x   =   -12

   Comprobación    
-11(-12)+12   =   144
132+12   =   144
144   =   144
        
 
Ejercicio 3         
-8x-15   =   -111
-8x   =   -111+15      
-8x   =   -96
x   =   -96/-8
x   =   12

   Comprobación    
-8(12)-15   =   -111
-96-15   =   -111
-111   =   -111
        
 
Ejercicio 4         
6x-10   =   -16
6x   =   -16+10      
6x   =   -6
x   =   -6/6
x   =   -1

   Comprobación    
6(-1)-10   =   -16
-6-10   =   -16
-16   =   -16